Design of optimal sequential hybrid testing plans. (16th April 2021) - Cheng, Yao; Elsayed, Elsayed A.
Abstract: One-shot units are produced in batches and stored in either a dormant or standby mode until retrieved or activated to perform their function when needed. In this article, we propose hybrid reliability testing approaches to utilize the advantages of non-destructive testing and destructive testing for assessment of reliability metrics. Specifically, we design a sequence of optimal hybrid testing plans under flexible scenarios. Extensive simulation models are developed to validate the accuracy and efficiency of the proposed approaches.